2017
DOI: 10.1175/jas-d-17-0006.1
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of the Predictability of Mesoscale Convective Systems on the Horizontal Scale and Amplitude of Initial Errors in Idealized Simulations

Abstract: Recent work has suggested that modest initial relative errors on scales of O(100) km in a numerical weather forecast may exert more control on the predictability of mesoscale convective systems at lead times beyond about 5 h than 100% relative errors at smaller scales. Using an idealized model, the predictability of deep convection organized by several different profiles of environmental vertical wind shear is investigated as a function of the horizontal scale and amplitude of initial errors in the low-level m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 33 publications
3
43
0
Order By: Relevance
“…The bias can result in a systematic drift from large-scale patterns (Cha & Lee, 2009;Miguez-Macho et al, 2004;Vincent & Hahmann, 2015) due to significant distortion of large-scale baroclinic wave propagation (Guidard & Fischer, 2008;Miguez-Macho et al, 2004). In addition, the large-scale error can quickly propagate to all scales through a rapid error growth process (Weyn & Durran, 2017), causing small-scale convective systems to lose predictability within a short period (Durran & Weyn, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The bias can result in a systematic drift from large-scale patterns (Cha & Lee, 2009;Miguez-Macho et al, 2004;Vincent & Hahmann, 2015) due to significant distortion of large-scale baroclinic wave propagation (Guidard & Fischer, 2008;Miguez-Macho et al, 2004). In addition, the large-scale error can quickly propagate to all scales through a rapid error growth process (Weyn & Durran, 2017), causing small-scale convective systems to lose predictability within a short period (Durran & Weyn, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recently published papers, the predictability and various causes of the loss of predictability of other hazards related to severe storms, including tornadoes, heavy rainfall, severe convective winds, and tropical cyclones, have been quantified using ensemble simulations (Durran & Weyn, ; Emanuel & Zhang, ; Fernández‐González et al, ; Flora et al, ; Miglietta et al, , ; Munsell et al, ; Nielsen & Schumacher, ; Weyn & Durran, , ; Zhang et al, , ; Zhang & Tao, ). For example, the practical and intrinsic predictability of a tornadic supercell have been explored from the perspective of convection initiation time, which was strongly modulated by the evolution of the planetary boundary layer, and local topography (Zhang et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the amplitude of the initial condition errors can improve predictability lead times, but this improvement diminishes with further reductions in the error amplitude. This suggests a limit to the intrinsic predictability of mesoscale convective systems, which are often thought to be particularly effective at transferring small‐scale perturbations to larger scales (Weyn & Durran, ; Zhang et al, ). In Zhang et al (), a tornadic supercell's intrinsic predictability limit was found to be 3–6 hr using an ensemble generated from small‐magnitude perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations